Slovene Immigrants and their Descendants in North America: Faces of Identity - Šabec, Nada (2021)
The monograph consists of two complementary parts: the first presents the author's research on Slovene American and Canadian communities, the second narratives by the immigrants and their descendants themselves. Language use and attitudes of Slovene Americans and Canadians as well as the relationship between their sense of ethnic identity and the degree of mother tongue maintenance is examined. A rapid shift from Slovene to English is observed across generations. Language choice both on individual and community levels is  explained within the Communication Accommodation theory (Giles and Ogay 2007).  Despite the relatively high symbolic value that the participants attribute to Slovene, it is not central to their ethnicity. The most important ethnic identification factor is culture in its broadest sense (from customs to sense of belonging). The majority feels more bicultural than bilingual, American and Canadian, but also Slovene, which they perceive as a source of pride and an enrichment of their lives.
Keywords: Slovene-English language contact; ethnic and cultural identity; language maintenance and shift; immigrant narraratives; Slovene Americans; Slovene Canadians